Создание методики определения линий энергопотребления предприятия - Сафьянц, Сергей Матвеевич; Бирюков, Алексей Борисович; Сафьянц, Артем Сергеевич (НТУ "ХПИ", 2016)
Цель работы состоит в предложении единой методологии для построения линий энергопотребления предприятия, так как простой удельный расход энергии, отнесенный к объему производства не может служить хорошим индикатором. В работе даются определения энергоэффективности предприятия и её показателей; рассматривается выбор показателей, влияющих на использование энергии; раскрывается сущность базовой линии энергопотребления, описывается методика её определения для технологической и инфраструктурной составляющей в агрегатах и технологических линиях предприятия; предлагается способы сравнения эффективности работы различных предприятий.

The aim of this paper is to provide a general methodology for determination of an energy baseline of an enterprise. It is important goal because nowadays all the industrial enterprises have their own criteria’s of energy efficiency and energy performance indicators, which make impossible comparison and benchmarking of these ones. At the same time simple specific energy consumption related to a volume of production can not serve as a good indicator. So, at the first hand. This paper contains definitions for the energy efficiency of the enterprise and its energy performance indicators as characterization of the energy efficiency in industrial processes, determined by comparing the values of the specific energy efficiency of these processes with similar indicators selected as a reference.
Creating a methodology for determination of the energy baseline of an enterprise
Keywords: энергоэффективность; система энергоменеджмента; показатели энергоэффективности; бенчмаркинг; energy efficiency; energy management system; energy performance indicators